(untitled) (Journal of the College of Basic Education, 2025)
Coagulase is one of the important enzyme produced by pathogenic strains of Staphylococcus that has been used as a marker to classify them into coagulase-positive - (CoP) or coagulase-negative staphylococci (CoNS), that affects the clotting mechanism of blood. This enzyme reacts with prothrombin, which then clots the plasma or serum. The aim from this study is the determine the anti- biofilm activity of Coagulase purified from Staphylococcus.aureus on five different local clinical bacterial isolates from wound and vagina swab from Al-Shahed Alsadder Teaching Hospital and Ibn Al-Baladi Hospital from 1 December 2023 unitl 15 April 2024 that was biofilm former : P.aeruginosa ,E. coli , S,aureus , S. pneumonieand Candida. albicans.; Coagulase was used at different concentration ( 4,2,1,0.5,0.25,0.12, 0.06 mg/ml ).twenty hundred samples from various clinical sources were collected from hospitals throughout Baghdad, and under aseptic lab conditions,about One hundred thirty single isolates were identified . The optimum condition of coagulase enzyme is pH-7.5, temperature 37C is the ideal environment for Staphylococcus.aureus to produce Coagulase . The crude Coagulase extracted had an activity of 1.7 (U/ml) and a specific activity of (U/mg). The enzyme was purified by precipitating it with ammonium sulphate at a saturation level of 50-80% and utilizing SDS-PAGE. Further purification was achieved using ion exchange chromatography using DEAE cellulose and gel filtering using Sephadex G150. The molecular weight of the Coagulase enzyme was found to be 36 kilodaltons (KD).